Решение обратной задачи бокового каротажного зондирования в условиях терригенного разреза - Миронцов, М.Л. (Доповіді НАН України, 2020)
На примере бокового каротажного зондирования показана возможность оценки влияния вмещающих пластов и граничных эффектов на реальную вертикальную разрешающую способность решения обратной
задачи. Показана возможность улучшения такой способности при помощи нового подхода к решению обратной задачи, позволяющего учитывать количественный вклад измерения каждого зонда в окончательный
результат. Приведен пример такого решения обратной задачи комплекса “БКЗ+БК” для реального скважинного материала в терригенном разрезе. На прикладі бокового каротажного зондування показана можливість оцінки впливу вміщуючих пластів і
граничних ефектів на реальну вертикальну роздільну здатність розв'язання оберненої задачі. Показана
можливість покращення такої здатності за допомогою нового підходу до розв'язання оберненої задачі,
який дозволяє враховувати кількісний вклад вимірювання кожного зонда в остаточний результат. Наведено
приклад такого розв'язання оберненої задачі комплексу “БКЗ+БК” для реального свердловинного матеріалу у теригенному розрізі. Using the example of lateral logging sounding, the possibility of assessing the influence of the adjacent beds and
boundary effects on the real vertical resolution of the inverse problem is shown. It is shown how it is possible
to improve this ability using a new approach to solving the inverse problem, which allows one to account for the
quantitative contribution of the measurement of each probe to the final result. An example of such solution to
the inverse problem of the “BKZ+BK” complex for a real well material in a terrigenous section is given. The following
conclusions are made: for the correct use of the algorithm for solving the inverse problem, it is necessary
to have an estimate of the vertical resolution of the electrometry method as a whole; a real assessment of the influence
of boundary effects on the measurement of the apparent resistance of the probes of the complex allows us
to evaluate the effectiveness of the method; the use of the proposed residual functional allows us to change the
effect of probes of different lengths on the final result and thereby allows us to achieve a satisfactory accuracy
even when studying the geoelectric parameters of formations whose power is less than the length of the largest probes of the electrometric complex. The results of the work were introduced into the production of a number of commercial geophysical organizations.